Graduating at the wrong time: Labor market outcomes of colleges graduates during economic contraction - Al Ayyubi, Muhammad Salahudin; Pratomo, Devanto Shasta (Jurnal Ekonomi Indonesia, 2025)
The severe economic contraction caused by the COVID-19 pandemic has led to high unemployment rates among college graduates. Fresh graduates entering the labor market are often highly sensitive to prevailing economic conditions. The impact of graduating at an unfavorable time can also vary significantly among workers, depending on their field of study. This study has two main objectives. First, it examines the effect of graduation timing, proxied by the unemployment rate, on labor absorption in Indonesia and how long these effects persist. Second, it analyzes the differences in job market sensitivity across disciplines among college graduates in Indonesia, particularly during economic contractions. The data used in this study come from the 2021 Indonesian National Labor Force Survey (Sakernas). The findings indicate that those who graduate during unfavorable economic conditions tend to experience significant income declines for over 10 years. Moreover, they face lower chances of obtaining decent jobs and are more likely to be overeducated for their roles. Additionally, college graduates from STEM (Science, Technology, Engineering, and Mathematics) fields experience less income compared to those from social sciences and humanities disciplines. The findings of this study are expected to provide valuable insights for policymakers in promoting income stability, aligning education with labor market demands, ensuring equal access, and fostering cross-disciplinary inclusivity. These efforts could contribute to developing a resilient and adaptive workforce capable of overcoming economic challenges and supporting sustainable economic growth. Keywords: labor market; unemployment rate; STEM; income JEL Classification: J24; J21; E32